2011
DOI: 10.1074/jbc.a110.199448
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine oxidation within N-terminal mutant huntingtin promotes oligomerization and delays clearance of soluble protein.

Abstract: We suggest that subscribers photocopy these corrections and insert the photocopies in the original publication at the location of the original article. Authors are urged to introduce these corrections into any reprints they distribute. Secondary (abstract) services are urged to carry notice of these corrections as prominently as they carried the original abstracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Cys106 is subject to modification during oxidative stress, and its oxidation has been proposed to be an important post-translational modification that may allow DJ-1 to act as a cellular redox sensor or to regulate interactions with its binding partners. , However, the detailed mechanism by which cysteine oxidation alters DJ-1 function is unclear, particularly because the crystal structures of the reduced and Cys106-SO 2 – proteins are essentially identical. , Our results show that both the human and insect proteins are substantially stabilized by oxidation of the reactive cysteine to the cysteine-sulfinate. The stabilization contrasts with many other proteins where cysteine oxidation to the sulfinate or sulfonate is associated with destabilization. , When considered in the context of previous evidence that oxidation of Cys106 in human DJ-1 leads to protein destabilization, our observations strongly suggest that it is the formation of the more highly oxidized cysteine-sulfonate (Cys106-SO 3 – ) that disrupts DJ-1 stability. This is consistent with some previously proposed models , and indicates that DJ-1 stability is biphasically regulated by oxidative cysteine modification.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Cys106 is subject to modification during oxidative stress, and its oxidation has been proposed to be an important post-translational modification that may allow DJ-1 to act as a cellular redox sensor or to regulate interactions with its binding partners. , However, the detailed mechanism by which cysteine oxidation alters DJ-1 function is unclear, particularly because the crystal structures of the reduced and Cys106-SO 2 – proteins are essentially identical. , Our results show that both the human and insect proteins are substantially stabilized by oxidation of the reactive cysteine to the cysteine-sulfinate. The stabilization contrasts with many other proteins where cysteine oxidation to the sulfinate or sulfonate is associated with destabilization. , When considered in the context of previous evidence that oxidation of Cys106 in human DJ-1 leads to protein destabilization, our observations strongly suggest that it is the formation of the more highly oxidized cysteine-sulfonate (Cys106-SO 3 – ) that disrupts DJ-1 stability. This is consistent with some previously proposed models , and indicates that DJ-1 stability is biphasically regulated by oxidative cysteine modification.…”
Section: Discussionmentioning
confidence: 52%
“…The stabilization contrasts with many other proteins where cysteine oxidation to the sulfinate or sulfonate is associated with destabilization. 71,72 When considered in the context of previous evidence that oxidation of Cys106 in human DJ-1 leads to protein destabilization, 39 our observations strongly suggest that it is the formation of the more highly oxidized cysteine-sulfonate (Cys106-SO 3…”
Section: ■ Discussionmentioning
confidence: 79%
“…This is consistent with other suggestions of altered one‐carbon metabolism, such as the increases in DNA and histone methylation . Since there is normally an equilibrium between methionine and cysteine, this finding could also be connected to alterations in L‐cysteine levels that have been reported in HD and related to oxidative mechanisms of pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of metal homeostasis in the progression of HD has been identified, with increased iron levels observed in the striatum (Bartzokis et al., ), and copper levels are also increased in the CNS of human HD brains, HD animal models (Dexter et al., , ; Perez et al., ; Fox et al., ). In vitro studies show that the fragment containing the first 171 amino acids of human wild‐type Htt and its glutamine‐expanded mutant form directly interacts with and reduces copper and iron (Fox et al., , ). While Htt protein has yet to be inconclusively identified in EVs, several proteomic studies have identified Htt in exosomes via mass spectrometry (Miguet et al., ; Wang et al., ; Fraser et al., ; Meckes et al., ; Skogberg et al., ).…”
Section: Introductionmentioning
confidence: 99%